Analisis Prediksi Kebangkrutan PT. Mayora Indah Tbk Periode 2022-2024 dengan Metode Altman Z-Score - Rizky, Gioni Raisya Naylamadina; Hulu, Dalizanolo (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to assess the financial condition of PT Mayora Indah Tbk for the period 2022–2024 using the Altman Z-Score method, which consists of five key financial ratios: X1 (Working Capital to Total Assets), X2 (Retained Earnings to Total Assets), X3 (EBIT to Total Assets), X4 (Market Value of Equity to Total Debt), and X5 (Sales to Total Assets). The results indicate that the company consistently remained in the Safe Area over the three-year period, with Z-Score values of 2.99 in 2022, increasing to 6.92 in 2023, and remaining strong at 5.91 in 2024. These findings demonstrate that the company faces a low risk of bankruptcy and maintains stable financial performance. Overall, PT Mayora Indah Tbk is in solid financial condition and shows good prospects for business sustainability throughout the analysis period.